PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (Studi pada Kantor Sekretariat Daerah Kabupaten Grobogan) - Saputri, 15.05.51.0053; Priyono, Bambang Suko (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the influence of Leadership, Work Environment and Work Culture on Employee Performance. The object of research in this paper is at the Regional Secretariat Office of Grobogan Regency. The population in this study were all employees of the Regional Secretariat Office of Grobogan Regency by distributing using census or saturated sampling methods. The questionnaire data collection technique in this study used a Likert scale. The results of this study are: leadership has no influence on employee performance, work environment partially has a positive and significant effect on employee performance, and organizational culture partially has a positive and significant effect on employee performance. From these results it can also be concluded that simultaneously leadership variables, work environment and organizational culture have an influence on employee performance which is more dominated by organizational culture variables.